Ultra-wideband solar absorber based on refractory titanium metal. (October 2020) - Yu, Peiqi; Yang, Hua; Chen, Xifang; Yi, Zao; Yao, Weitang; Chen, Jiafu; Yi, Yougen; Wu, Pinghui
Abstract: Electromagnetic wave absorbers with very long absorption spectra have become an important target for optoelectronic materials and technology. In this paper, we propose a titan-based resonator to achieve near-perfect wide spectrum absorption of solar radiation. In the whole spectrum of the study, the average absorption of the absorber is up to 93.17%. Using surface plasmon resonance, up to 1759 nm in the range of absorption over 90% in the absorption spectrum studied (166.8–1926.6 nm). Furthermore, the absorption spectrum of the absorber is not sensitive to polarization. Since the material constituting the absorber is a mainly refractory metal, it can work under a complex electromagnetic environment (solar radiation) and high-temperature conditions. Later, the influence of various parameters on the absorption spectrum and the mechanism of forming broadband absorption was explored. It is also found that other refractory metals similar to titanium have a good effect on the absorber with this structure. Graphical abstract: We report a numerical study of an ideal solar broadband absorber based on refractory titanium. By optimizing the design, the average solar absorption efficiency of the absorber in the studied wavelength range (100–2000 nm) is as high as 93.17%. Image 1 Highlights: The absorber is capable of obtaining ultra-wide spectrum absorption of solar energy. The absorbency of the absorber can be adjusted by optimizing the structural parameters. The absorber is insensitive to changes in the angle of incidence and polarization. The absorber has certain versatility to other refractory materials.